CHALLENGES OF FIQH TEACHERS IN DEVELOPING HOTS-BASED ASSESSMENTS: A CASE STUDY IN INDONESIAN ISLAMIC SENIOR HIGH SCHOOL - Risni, Titin Widya; Hendy; Khotimah, Adinda Khusnul (Published by the Islamic Religious Education Study Program Faculty of Tarbiyah and Teacher Training Kiai Haji Achmad Siddiq University, Jember, East Java, Indonesia, 2025)
The low critical thinking performance of Indonesian students, as highlighted by PISA and World Bank reports, underscores the urgency of implementing Higher Order Thinking Skills (HOTS) in assessment practices. While HOTS-based evaluation is emphasized in the Merdeka Curriculum, its application in Islamic subjects, particularly fiqh, remains underexplored. This study investigates the process and challenges faced by fiqh teachers in developing HOTS-based assessments at an Islamic senior high school in Indonesia. Employing a qualitative case study, data were gathered through classroom observation, semi-structured interviews, and document analysis, then analyzed using an interactive model with triangulation for validation. Findings indicate that teachers follow standard steps—competency analysis, blueprint design, stimulus development, item writing, and rubric construction—but encounter significant barriers, including limited mastery of Bloom’s Taxonomy, difficulties in creating contextual stimuli, dependence on textbooks, and lack of training. This study highlights the need for targeted professional development to strengthen teachers’ capacity in designing HOTS-oriented assessments. Rendahnya kemampuan berpikir kritis siswa Indonesia yang ditunjukkan oleh laporan PISA dan Bank Dunia menegaskan urgensi penerapan Higher Order Thinking Skills (HOTS) dalam praktik evaluasi. Meskipun Kurikulum Merdeka menekankan pentingnya penilaian berbasis HOTS, penerapannya pada mata pelajaran keagamaan, khususnya fikih, masih jarang dikaji. Penelitian ini bertujuan menganalisis proses penyusunan serta tantangan guru fikih dalam mengembangkan soal berbasis HOTS di salah satu madrasah aliyah di Indonesia. Metode yang digunakan adalah kualitatif studi kasus dengan teknik pengumpulan data melalui observasi, wawancara semi-terstruktur, dan analisis dokumen. Data dianalisis secara interaktif dengan uji keabsahan melalui triangulasi. Hasil penelitian menunjukkan bahwa guru mengikuti tahapan umum—analisis kompetensi, penyusunan kisi-kisi, pengembangan stimulus, penulisan soal, dan penyusunan rubrik—namun menghadapi hambatan serius, seperti keterbatasan penguasaan Taksonomi Bloom, kesulitan merancang stimulus kontekstual, ketergantungan pada buku teks, serta minimnya pelatihan. Temuan ini menegaskan perlunya pengembangan profesional berkelanjutan bagi guru untuk memperkuat kapasitas dalam merancang penilaian berbasis HOTS.